Incremental cost–effectiveness of percutaneous versus surgical closure of atrial septal defects in children under a public health system perspective in Brazil. (November 2014) - Costa, Rodrigo; Pedra, Carlos AC; Ribeiro, Marcelo; Pedra, Simone; Ferreira-Da-Silva, André Luis; Polanczyk, Carisi; Berwanger, Otávio; Biasi, Alexandre; Ribeiro, Rodrigo
<x xml:space="preserve">Abstract</x> Introduction: Cost–effectiveness (CE) studies of percutaneous (PC) versus surgical (SC) atrial septal defect closure are lacking. Methods: A systematic literature review in children and a CE analysis based on a model of long-term outcomes were performed. Direct costs of PC and SC were US8700 (defined arbitrarily) and US5700 (actually paid), respectively. Three-times the Brazilian GDI (US28, 700) per year of life saved (with a discount rate of 5%) was used as a limit for willingness-to-pay. Discussion: PC had a high (US104, 500) incremental CE ratio despite lower complication rates, shorter hospital stay and better (nonsignificant) adjusted life expectancy. PC would be cost–effective if it cost US6400 or SC had an 8% loss of utility or its indirect costs were US2250. Costs of PC should be reduced to be cost–effective in the Brazilian public health system. Indirect costs and impact on quality of life should be further assessed.